THE ROLE OF WORD-OF-MOUTH IN MEDIATING PRODUCT QUALITY TOWARDS CONSUMER PURCASE INTENTION ON ALISSA HIJAB - Aghivirwiati, Gusti Ayu (Buletin Studi Ekonomi, 2022)
This study aims to determine the influence of product quality in terms of word of mouth and purchase decisions, the influence of word of mouth and purchasing decisions and the role of word of mouth mediating the influence of product quality on the purchasing decision of Alissa hijab online shop in Denpasar city. The study was conducted by 120 respondents of female sex in Denpasar city who had purchased Alissa Hijab products. The number of respondents was determined using the purposive sampling method, namely the sample determination technique using certain criteria. The data was obtained by distributing a questionnaire that was analyzed using path (path analysis) and a Sobel test. The test results state that the product quality variable has a positive and significant effect on the word of mouth, the product quality variable has a positive and significant effect on purchase satisfaction, the word-of-mouth variable has a significant positive effect on purchasing turnover, and the word-of-mouth variable significantly mediates product quality to purchasing decisions.